A non-resonant, gravity-induced micro triboelectric harvester to collect kinetic energy from low-frequency jiggling movements of human limbs - Lu, Yingxian; Wang, Xiaohong; Wu, Xiaoming; Qin, Jin; Lu, Ruochen (Journal of micromechanics and microengineering, 2014)
This paper presents a non-resonant, gravity-induced micro triboelectric harvester with high internal resistance. The device collects kinetic energy from low-frequency jiggling movements for the power supply of portable electric devices such as wristwatches. It includes a friction module to produce triboelectric charge and an electrostatic induction module to export energy. The friction that transfers charge is induced by jiggling movements, with gravity and inertia of an internal slider, instead of with external direct force. The non-resonant structure allows the device to respond to low frequencies of 1.5-5.5 Hz, covering the frequencies of human motion. Load resistance sweeping shows that the optimal load resistance is about 1.1 GΩ, with the peak output voltage of about 260 V, and the output power of 60 µW. The proposed harvester responds to low-frequency kinetic energy in jiggling movements matching that of a human limb's running motion; so it has potential to convert the mechanical energy of arm swings or strides into electric energy.